Potential of mine waste material for mineral carbonation process in carbon capture and utilization application - M. Molahid, Verma Loretta (2022)
Mining activities may pose risks to its surrounding environment and population due to contaminant release and mine waste generation, while mining industry itself is considered as one of the carbon-extensive industries that contributes to the increasing carbon dioxide emission to the atmosphere. Carbon sequestration through mineral carbonation is one of the ways to mitigate these problems. Mineral carbonation can be explained by the reaction of carbon dioxide with silicate minerals forming stable carbonate. Mine waste has variety of potential minerals which can be utilized as the source of silicate minerals for carbonation. Therefore, this study focuses on the potential of the alkaline mining waste for carbon sequestration which involves the process of mineral carbonation. Throughout this study, characterization of the samples from three sites (i.e. gold mine, iron mine and limestone quarry) were performed and this includes particle size distribution (PSD) analysis, pH analysis, and chemical, mineralogical and morphological analyses. Mineral carbonation experiment was carried out under low pressure-temperature conditions using a designated stainless steel reactor. Results of pH analysis showed that most of the samples have an alkaline nature which shows its suitability for undergoing mineral carbonation reaction. Moreover, particle size distribution analysis for fine particles reveals the presence of large amounts of small-size particles (silt fraction) in gold mine waste which makes it suitable for this process. On the other hand, the iron mine waste consists of a large amount of large-sized particles (sand) indicating that pre-treatment needs to be done in order for the carbonation process to be optimized. Based on mineralogical analysis performed, all mine waste samples from the three mining sites contain minerals needed for the formation of carbonates where all of these minerals contain the important oxide or silicate minerals of calcium, magnesium and iron to enable the carbonation process. The chemical composition of all samples from three sites shows the presence of magnesium oxide (MgO) and iron oxide (Fe2O3) i.e. 1.74%-2.72% and 3.04%-11.79%, respectively in gold mine waste, iron oxide (Fe2O3) and calcium oxide (CaO) i.e. 39.58%-62.95% and 7.19%-15.24%, respectively in iron mine waste, and calcium oxide (CaO) and magnesium oxide (MgO) i.e. 72.12%-82.88% and 3.49%-4.36%, respectively in limestone waste rocks with high percentage showing high potential in sequestering and capturing carbon dioxide. Finally, the carbonation efficiencies (ranging from 2.11% to 3.97%) and carbon uptake results of 56.09-363.33 g CO2/kg reveals that smaller particle size of less than 38 μm, pH 8-12 in low temperature (80 °C) is ideal for the carbonation process to occur with maximum uptake capacity obtained of 87.66 g CO2/kg and 363.3 g CO2/kg for iron mine waste and limestone waste, respectively. From the mineral carbonation process, 0.46 g FeCO3/kg and 1.65 g CaCO3/kg have been successfully sequestered from the iron mine waste and limestone waste, respectively. Presence of carbonation product was confirmed by its morphological structure as needle-shaped crystal which was identified as aragonite in limestone waste. Statistical analysis shows that there was a statistically significant difference (p<0.05) in mean ranks between 38 μm and 75 μm, and a statistically significant, negative correlation between conversion efficiency (%) and particle size used (r= -0.487, p = 0.006). This indicates that particle size fraction is a crucial parameter in the carbonation process, and that using smaller particle size fraction can increase the carbonation efficiency. Findings show that these waste material have high potential to act as carbon sinks via mineral carbonation process. In line with the sustainable development goals in combating climate change, this study proposes a sustainable way towards low-carbon industry while making profit with the value-added carbonate produced. Therefore, this study is important to help tackle the issues of carbon emissions and strategy for carbon dioxide reduction in the future.